Cocoplum (Chrysobalanus icaco L.) Identification and Uses - Stephen Henry Brown; Marc S. Frank (EDIS)
Cocoplum is one of two native Florida plants in the Chrysobalanaceae family, and is found in a variety of habitats. This 9-page document discusses the identification and uses of cocoplum. Written by Stephen H. Brown and Marc S. Frank and published by the UF/IFAS Environmental Horticulture Department, March 2018. http://edis.ifas.ufl.edu/ep553